One-pot multicomponent synthesis of tetrahydropyridines promoted by luminescent ZnO nanoparticles supported by the aggregates of 6, 6-dicyanopentafulvene. Issue 8 (10th December 2014) - Kataria, Meenal; Pramanik, Subhamay; Kumar, Manoj; Bhalla, Vandana
Abstract : Aggregates of 6, 6-dicyanopentafulvene derivative4 serve as reactors and stabilizers for the preparation of ZnO NPs, which exhibit high catalytic efficiency in one-pot multicomponent synthesis of tetrahydropyridines. Abstract : Pot-shaped fluorescent aggregates of 6, 6-dicyanopentafulvene derivative4 serve as reactors and stabilizers for the preparation of luminescent ZnO nanoparticles, which exhibit high catalytic efficiency in one-pot multicomponent synthesis of tetrahydropyridines.